Respuesta :

Hey friend, hope I can assist you!
I will solve by elimination <3.
Multiply 3x - 7y = 2 by 2: 6x - 14y = 4
6x - 14y = 4
6x - 9y = 9
5y = 5
Now we have
6x - 14y = 4
5y = 5
Now we want to solve 5y = 5 for y
So simply divide both sides by 5.
5y/5 = 5/5
This gives us one or in other words, y = 1.
Now we want to plug y = 1 into  6x - 14y = 4
So 6x - 14 * 1 = 4
This gives us
6x - 14 = 4
Now add 14 to both sides.
6x - 14 + 14 = 4 + 14
6x = 18
Now divide both sides by 6
6x/6 = 18/6
This gives us 3 so x = 3
Therefore our solutions to this system of equations would be y = 1 and x = 3

ACCESS MORE